TRANSFORMASI DIGITAL WARISAN BUDAYA LOKAL: PEMERTAHANAN DAN PELESTARAIAN NILAI KEARIFAN LOKAL DI KAWASAN TELUK TOMINI - Nonny Basalama; Zulkifli Tanipu; Salam Tolaki; Herson Kadir; Ikha Hardiyanti Puspita Mahading (LPPM Universitas Abdurrab, 2024)
Tomini Bay is rich in local cultural heritage, Including traditional arts and local wisdom passed down from generation to generation. However, amidst the waves of globalization and modernization, this cultural heritage faces significant threats. The lack of documentation and limited technological infrastructure in remote areas have made efforts to preserve the culture increasingly challenging. Recognizing this situation, our community service initiative was launched with the hope of assisting the people of Teluk Tomini in preserving and sustaining their cultural heritage. We began with a straightforward outreach, introducing technology to the community so they could document their local culture, including traditional dances, music, folklore, and other valuable artifacts. With the help of the community, we successfully captured this cultural wealth in digital formats such as video, audio, and photographs. Additionally, we developed a digital platform that allows this cultural heritage to be accessed not only by the local community but also globally. The impact of this initiative has been significant. The younger generation has become more aware of the importance of preserving their cultural heritage. However, technological barriers, such as limited internet access, remain a major challenge. We recognize that ongoing efforts are needed to overcome these obstacles, so the people of Teluk Tomini can continue to play an active role in safeguarding their cultural legacy. Through regular evaluation and monitoring, we continuously assess the success of the platform’s implementation. Our hope is that technology can serve as a bridge connecting the past and the future, ensuring that Teluk Tomini's cultural heritage remains vibrant in the face of modern advancements.